Industrial Policy and Export Productivity: Analysis by Company Size and Microregions - Orsolin-Teixeira, Felipe; Nogueira, Mauro Oddo (Panoeconomicus, 2025)
This study aimed to investigate the possible spatial relationship between resources granted by the Brazilian Development Bank (BNDES) disaggregated by company size and export productivity in Brazil’s micro-regions. The study period was between 2009 and 2020. Data showed that most BNDES resources earmarked for the manufacturing industry were concentrated in the South and Southeast, particularly in the microregions close to the main commercial centers. By contrast, a pattern of low intensity in financing and productivity was observed in the microregions located in the country’s central area. The econometric results indicate the spatial spillover effects of BNDES financing on microenterprise export productivity across various microregions. Additionally, network analysis revealed that the microregions with the highest export volumes were not in the main cluster, indicating that they mainly exported simple or low-productivity products.JEL: O47, L52, C31.